Habitat enhancements rescue bee body size from the negative effects of landscape simplification. Issue 9 (23rd July 2019) - Grab, Heather; Brokaw, Julia; Anderson, Elisabeth; Gedlinske, Lauren; Gibbs, Jason; Wilson, Julianna; Loeb, Greg; Isaacs, Rufus; Poveda, Katja
Abstract: The negative effects of landscape simplification on bee communities are well documented. To reverse these effects, flowering habitat enhancements are designed to provide supplemental nutritional resources for wild bees and are particularly important when few resources are available in the surrounding landscape. Yet, it is not known whether or how habitat enhancements support bee populations under varying landscape contexts. Body size is a morphological trait that is strongly linked to foraging ability, immune function, and fitness in bees. Landscape simplification has been associated with size declines across bee taxa and smaller body size can be an early indicator of environmental stress. To determine whether the negative effects of landscape simplification on body size can be improved by adding floral resources to farm landscapes, we measured the body size of 10 wild bee species collected at 70 sites with or without habitat enhancements in Michigan and New York. Bees were collected at sites with varying amounts of agriculture in the surrounding landscape, allowing us to test whether morphological responses to enhancements are affected by landscape simplification. Half of the bee species measured exhibited declining body size across the landscape gradient. Among these species, declines were buffered by the presence of habitat enhancements suggesting this response is the result of improved nutrition, reduced need for long‐distance foraging, enhanced recruitment of larger individuals or a combination of these mechanisms. Declines in body size were strongest in both the smallest and the largest species. Large and medium sized species exhibited the greatest response to flowering habitat enhancements. Synthesis and applications. At sites with high agricultural cover, we observed intraspecific body size declines among many species; however, we did not observe decreased body size in any species at sites with a flowering habitat enhancement. Therefore, our findings suggest that the presence of flowering habitat enhancements can support wild bees experiencing stress from intensively managed agricultural landscapes across multiple cropping systems and regions. Abstract : At sites with high agricultural cover, we observed intraspecific body size declines among many species; however, we did not observe decreased body size in any species at sites with a flowering habitat enhancement. Therefore, our findings suggest that the presence of flowering habitat enhancements can support wild bees experiencing stress from intensively managed agricultural landscapes across multiple cropping systems and regions.